Synthesis of pyridine and furan based arylated ketones through palladium catalyst with DFT study of their static and frequency dependent NLO response - Shehzadi, Kiran; Tariq, Ayesha; Zubair, Muhammad; Mahmood, Tariq; Kosar, Naveen; Karakaya, Idris; Rasool, Nasir (Elsevier, 2023)
A series of pyridine and furan based ketones have been synthesized by Suzuki coupling of 2,6-pyridinedicarbonyl dichloride, furan-2-carbonyl chloride with various aryl boronic acids in existence of catalyst Pd(PPh3)4 and cesium carbonate in presence of toluene at 100 degrees C. The compounds were synthesized in good to high yields. Various functional moities were well tolerated under developed conditions of reaction. DFT studies are used to illustrate insight of geometrical, electronic, reactivity descriptor parameters optical & nonlinear optical properties and nonlinear refractive index of all synthesized compounds (3a-3g and 4a-4h). 3c is kinetically less stable and moderately reactive among all these compounds. A highest beta o (1576.39 au) and nonlinear refractive index values are obtained for compound 3a where the strong electron withdrawing group (chloro-acyl group) is present at ortho position of the pyridine ring. According to the push pull mechanism, electronic displacement between electron donating and withdrawing groups through extended conjugation is responsible for change in nonlinear optical properties of the compound. Computational studies provide detail information about the synthesized compounds and their applicability in the field of organic reactivity, electronics, and optoelectronics for future work.
Keywords: Suzuki; Cross -coupling; Aryl ketones; Pyridine; Furan; Non-linear optical